Scheduling longer working lives for older aged care workers: A time and income capability approach. (3rd May 2020) - Hart, Aaron; Bowman, Dina; Mallett, Shelley
Like many other countries, Australian government policy focuses on extending working life as a response to concern about the cost of an ageing population. In this article, we focus on older aged care workers and highlight how poor employment conditions hinder their capacity to work in later life. Many of these workers are at risk of time and income poverty, since they are on low wage, part-time, low-hour contracts and need to pick up extra shifts to earn a living wage. The interactions between time poverty and income poverty have been developed within a body of literature that analyses the quantities of time individuals and households allocate to paid employment, household, family and caring responsibilities, sleep and self-care. Burchardt's notion of 'time and income capability' brings insights from this corpus into dialogue with the capabilities approach, a political philosophy that equates wellbeing with the breadth of realistic opportunities for people to do things that they have reason to value. This study uses Burchardt's construct to analyse qualitative data from interviews with 20 older personal care workers. While all the workers we spoke with engaged in self-sustaining practices, there were varying levels of opportunity to pursue them. Workers with less time and income capability found it more difficult to sustain themselves and their households. Some employer practices diminished workers' time and income capability: unrealistic workloads necessitating unpaid hours; providing little opportunity for input into rostering; and late-notice roster changes. When time and income capability was too low, workers' informal care duties, social connections and health were compromised. In the Australian aged care sector, several changes can enable longer working lives: sufficient paid hours to perform the role, wage loading for hours in addition to those contracted, written notice for roster changes, and increased wages.